2012
DOI: 10.1177/147323001204000416
|View full text |Cite
|
Sign up to set email alerts
|

High Anxiety, Young Age and Long Waits Increase the Need for Preoperative Sedatives in Children

Abstract: OBJECTIVE:This prospective, observational study aimed to identify children likely to require sedation preoperatively by measuring anxiety levels using the modified Yale Preoperative Anxiety Scale (mYPAS). Other possible predictive factors for preoperative sedation were also investigated. METHODS: A total of 455 patients aged 2 -12 years scheduled for surgery requiring general anaesthesia were enrolled in the study. Patients' anxiety levels were measured using the mYPAS in a preoperative holding area just befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…These data are consistent with limited data in the anesthesia literature assessing pre-operative anxiety. In a prospective study by Kim and associates [9], age, type of parent or guardian, number of siblings, waiting time and score on the modified Yale Preoperative Anxiety Scale (mYPAS) were assessed for predicting need for pre-operative sedation for anxiety in children prior to general anesthesia (GA). In multivariate analysis, age, mYPAS score and waiting time were significant factors related to anxiety levels requiring preoperative sedation.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with limited data in the anesthesia literature assessing pre-operative anxiety. In a prospective study by Kim and associates [9], age, type of parent or guardian, number of siblings, waiting time and score on the modified Yale Preoperative Anxiety Scale (mYPAS) were assessed for predicting need for pre-operative sedation for anxiety in children prior to general anesthesia (GA). In multivariate analysis, age, mYPAS score and waiting time were significant factors related to anxiety levels requiring preoperative sedation.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings from previous literature. 34,38 In children, the perception of anxiety depends on the developmental stage and cognitive potential of the child; different responses can be observed among those facing the same stressor agent. With increasing age, the cognitive capacity of the child increases, resulting in more awareness, understanding, and more likely to overcome stress than younger children.…”
mentioning
confidence: 99%
“…33,40 On the contrary, other studies showed that children with previous surgery and anesthesia were significantly less anxious during the preoperative period. 37,38 The possible explanation for this may be children who had previous negative surgical and anesthetic histories (who suffer pain, light anesthesia) may exacerbate subsequent anesthesia and surgery-related anxiety. However, those who had a previous positive and smooth experience of previous surgeries may favor the sense of safety in the child because he/she already knows what to expect; they are dealing with something known, about the surgery and anesthesia which may attenuate anxiety in the subsequent surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior literature, children were categorized into the high anxiety group if their score was 40 or greater. 13…”
Section: Methodsmentioning
confidence: 99%